2022
DOI: 10.1186/s12920-022-01222-y
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression analysis to identify key modules and hub genes associated with COVID-19 in platelets

Abstract: Corona virus disease 2019 (COVID-19) increases the risk of cardiovascular occlusive/thrombotic events and is linked to poor outcomes. The underlying pathophysiological processes are complex, and remain poorly understood. To this end, platelets play important roles in regulating the cardiovascular system, including via contributions to coagulation and inflammation. There is ample evidence that circulating platelets are activated in COVID-19 patients, which is a primary driver of the observed thrombotic outcome.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 83 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…Several studies have applied WGCNA to identify the hub genes COVID‐19 patients, including the hub genes in the nasopharyngeal swabs between normal subjects and COVID‐19 patients, critical genes of age‐related module in the peripheral blood mononuclear cell of COVID‐19 patients, and key genes in the platelets of between health controls and COVID‐19 patients [ 24 , 25 , 26 ]. These studies explored the key genes of COVID‐19 from a variety of perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have applied WGCNA to identify the hub genes COVID‐19 patients, including the hub genes in the nasopharyngeal swabs between normal subjects and COVID‐19 patients, critical genes of age‐related module in the peripheral blood mononuclear cell of COVID‐19 patients, and key genes in the platelets of between health controls and COVID‐19 patients [ 24 , 25 , 26 ]. These studies explored the key genes of COVID‐19 from a variety of perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular vesicles or the circulating cell-free MT-ND1 content can be used as a tool to diagnose and detect cancer. MT-ND1 mRNA might also serve as a biomarker for T2D, and it has been verified to be downregulated in patients with diabetic kidney diseases [ 72 , 73 ]. In addition, mutations in MT-ND1 mutation-induced decreases in respiratory chain CI levels and/or enzyme activity are important genetic factors causing diseases such as LHON, MELAS, and T2D.…”
Section: The Application Of Mt-nd1 Mutations In Di...mentioning
confidence: 99%
“…In 2021, researchers found that MTRNR2L12 was upregulated in immune cells, such as CD8 + T cells, in bronchoalveolar lavage fluid from mild and severe COVID-19 patients (106), suggesting the possibility of altered expression following COVID-19 vaccination. Two recent papers published in 2022 found the differential expression of MTRNR2L12 in bronchoalveolar lavage fluid samples from patients with severe COVID-19 (107) and classification of the MTRNR2L12 gene as an important gene determining COVID-19 positive status by association classification model (108). Thus, COVID-19 vaccination may cause the differential expression of MTRNR2L12 and serve as a feature that facilitates the differentiation among the protective capacities of different vaccination strategies.…”
Section: Qualitative Features In Cd8+ T Cellsmentioning
confidence: 99%